Digital Marketing Sebagai Strategi Komunikasi Peningkatan Minat Nasabah Produk Tabungan Haji Di Era Digital (Studi Kasus: Bank Sumsel Babel Syariah) - Aswa, Nahdatul (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze service communication carriedoutbyfrontlinersat Bank Sumsel Babel Syariah in delivering information about banking products to customers. Service communication is a crucial aspect because frontliners serve as the direct representation of the institution in building customer understanding, trust, and interest in banking products. This research employs a descriptive qualitative approach, using data collection techniques such as structured interviews, observation, and documentation. The research subjects consist of tellers, customer service officers, andservice supervisors who are directlyinvolved in customer service activities. Data analysis is conductedusing the Integrated Marketing Communication (IMC) theory as an analytical framework to examine message consistency, communication integration, andcustomer-oriented service practices.The findings indicate that the service communication implemented by frontliners at Bank Sumsel Babel Syariah reflects the application of IMC principles, particularly in maintaining message consistency and clarity of information delivered to customers. Frontliners provide product information based on standardized guidelines, thereby reducing discrepancies in explanations among staff members. The two-way interaction established during the service process allows customers to receive information according to their needs while creating a positive service experience. Service communication is not merely informative but also plays a role in fostering trust and long-term relationships between the bank and its customers. This study concludes that consistent and integrated service communication is a key factor in supporting the effectiveness of information delivery in Islamic banking services